Reversed-Phase Liquid Chromatography of Peptides for Bottom-Up Proteomics: A Tutorial - Lenčo, Juraj; Jadeja, Siddharth; Naplekov, Denis K; Krokhin, Oleg V; Khalikova, Maria A; Chocholouš, Petr; Urban, Jiří; Broeckhoven, Ken; Nováková, Lucie; Švec, František (Journal of proteome research, 2022)
The performance of the current bottom-up liquid chromatography hyphenated with mass spectrometry (LC-MS) analyses has undoubtedly been fueled by spectacular progress in mass spectrometry. It is thus not surprising that the MS instrument attracts the most attention during LC-MS method development, whereas optimizing conditions for peptide separation using reversed-phase liquid chromatography (RPLC) remains somewhat in its shadow. Consequently, the wisdom of the fundaments of chromatography is slowly vanishing from some laboratories. However, the full potential of advanced MS instruments cannot be achieved without highly efficient RPLC. This is impossible to attain without understanding fundamental processes in the chromatographic system and the properties of peptides important for their chromatographic behavior. We wrote this tutorial intending to give practitioners an overview of critical aspects of peptide separation using RPLC to facilitate setting the LC parameters so that they can leverage the full capabilities of their MS instruments. After briefly introducing the gradient separation of peptides, we discuss their properties that affect the quality of LC-MS chromatograms the most. Next, we address the in-column and extra-column broadening. The last section is devoted to key parameters of LC-MS methods. We also extracted trends in practice from recent bottom-up proteomics studies and correlated them with the current knowledge on peptide RPLC separation.
Keywords: protein separation; peptide properties; hmotnostní spektrometrie; bottom-up proteomics; Peptides; Chromatography, Reverse-Phase; Chromatography, High Pressure Liquid; Mass Spectrometry; Proteomics; peptide separation; tutorial; vysokoúčinná kapalinová chromatografie; chromatografie s reverzní fází; proteomika; method development; reversed-phase liquid chromatography; peptidy